Studi Kitab Tafsir Tanwir Al-Miqbas Min Tafsir Ibni ‘Abbas oleh Al-Fairuzabadi - Hikmah, Farisa Aliyatul; Dahliana, Yeti; Nirwana, Andri; Suharjianto, Suharjianto; Azizah, Alfiyatul; Rha’in, Ainur (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
Tanwir al-Miqbas min Tafsir Ibni ‘Abbas by Al-Fairuzabadi is a classical tafsir (Quranic exegesis) that compiles the interpretative methodology of Ibnu ‘Abbas and offers a unique perspective in tafsir studies. This study aims to deepen understanding of the interpretative methodology in "Tanwir al-Miqbas," detailing how Ibnu ‘Abbas interpreted the Quran as compiled by Al-Fairuzabadi. Utilizing a qualitative approach and bibliographic research, this study relies on primary and secondary data sources for a descriptive analysis of Al-Fairuzabadi’s biography, interpretative methodology, as well as the strengths and weaknesses of "Tanwir al-Miqbas" tafsir. It reveals that this exegesis emphasizes a global (ijmali) explanation of Quranic verses using popular and accessible language, incorporating narrations of Ibnu ‘Abbas in interpretation. Although considered a tafsir bil ma'tsur, it exhibits broader exploration on certain verses. "Tanwir al-Miqbas" presents an important perspective in tafsir studies, merging ijmali and linguistic interpretative methodologies that directly refer to Prophet Muhammad. Despite questions regarding the validity of its sanad (chain of transmission), this work remains a significant contribution to Quranic exegesis literature.Abstract: Kitab Tanwir al-Miqbas min Tafsir Ibni ‘Abbas karya Al-Fairuzabadi merupakan salah satu tafsir klasik yang menghimpun metodologi penafsiran Ibnu ‘Abbas dan menawarkan perspektif unik dalam studi tafsir. Kajian ini bertujuan untuk memperdalam pemahaman tentang metodologi penafsiran dalam Tanwir al-Miqbas, menguraikan cara Ibnu ‘Abbas menafsirkan Al-Quran yang dikompilasi oleh Al-Fairuzabadi. Menggunakan pendekatan kualitatif dan penelitian kepustakaan, penelitian ini mengandalkan sumber data primer dan sekunder untuk analisis deskriptif tentang biografi Al-Fairuzabadi, metodologi penafsiran, serta kelebihan dan kekurangan tafsir Tanwir al-Miqbas. Kajian ini menunjukkan bahwa kitab tafsir ini menekankan penjelasan global (ijmali) ayat-ayat Al-Quran menggunakan bahasa yang populer dan mudah dipahami, menggabungkan riwayat Ibnu ‘Abbas dalam penafsiran. Meski dianggap sebagai tafsir bil ma'tsur, terdapat eksplorasi lebih luas pada ayat tertentu. Kitab Tanwir al-Miqbas menawarkan perspektif penting dalam studi tafsir, menggabungkan metodologi penafsiran ijmali dan linguistik yang merujuk langsung kepada Nabi Muhammad SAW. Meskipun ada pertanyaan mengenai validitas sanad, karya ini tetap berkontribusi signifikan dalam literatur tafsir Al-Quran